Arqueologia dos gestos na indústria lítica do sítio Colônia Miranda - Coutinho, Janaína Patrícia (2015)
Despite the archaeological potential present in Sergipe region, being the representative the site Justino located in the area of Xingó the valley of São Francisco, there are few studies regarding the pre-history of the state. Therewith new projects are in progress and one of them it is the archaeological survey of the basin the River Vaza Barris, where from it there was identification of the site Colonia Miranda, located in the city of Sao Cristovao, Sergipe state. Therewith this dissertation will work with the archeology of the gestures that searches through a structural analysis, based on of the anthropology of techniques possible technological aspects of the groups the past that occupied the region. Based on concepts like operating chain, total man, motor behaviors and habitus, this work will infer the relationship about the gesture and the influence of cultural tradition for the incorporation of techniques in the production stage and functioning.